Large‐Area Conductor‐Loaded PDMS Flexible Composites for Wireless and Chipless Electromagnetic Multiplexed Temperature Sensors - Benjamin King; Nikolas Bruce; Mahmoud Wagih (Advanced Science)
Abstract Capacitive dielectric temperature sensors based on polydimethylsiloxane (PDMS) loaded with 10 vol% of inexpensive, commercially‐available conductive fillers including copper, graphite, and milled carbon fiber (PDMS‐CF) powders are reported. The sensors are tested in the range of 20–110 °C and from 0.5 to 200 MHz, with enhanced sensitivity from 20 to 60 °C, and a relative response of 85.5% at 200 MHz for PDMS‐CF capacitors. PDMS‐CF capacitors are interrogated as a sensing element in wirelessly coupled chipless resonant coils tuned to 6.78 MHz with a response in the resonant frequency (fr) of the sensor, demonstrating an average sensitivity of 0.38% °C−1, a 40x improvement over a pristine PDMS capacitive sensor and outperforms state‐of‐the‐art frequency‐domain radio frequency temperature sensors. Exploiting its high sensitivity, the wireless sensing platform is interrogated using a low‐cost, portable, and open‐source NanoVNA demonstrating a relative response in fr of 48.5%, good agreement with instrumentation‐grade vector network analyzers (VNAs) and negligible change in performance at a range of reading distances and humidities. Finally, a wireless tag is demonstrated with rapid, reversible dynamic response to changes in temperature, as well as the in the first scalable, multiplexed array of chipless sensors for spatial temperature detection.